Hydrocarbon process safety : a text for students and professionals - Jones, J. C. 1952- (Whittles Pub., 2003)
Annotation Addressing the vitally important subject of process safety in the hydrocarbon industry, this text has a broad coverage which integrates various aspects so that the book will be readily accessible to readers of diverse backgrounds. A grasp of the material requires only familiarity with physical and organic chemistry (at first-year undergraduate level) and with heat transfer and fluid flow at the same level. The text is complemented by many numerical examples with full solutions.
Keywords: Hydrocarbons -- Refining -- Safety measures.; Petroleum industry and trade -- Safety measures.; Gas industry -- Safety measures.; elektronické knihy; electronic books